1997
DOI: 10.1073/pnas.94.14.7446
|View full text |Cite
|
Sign up to set email alerts
|

Position- and orientation-independent activity of the Schizosaccharomyces pombe meiotic recombination hot spot  M26

Abstract: The activity of the M26 meiotic recombination hot spot of Schizosaccharomyces pombe depends on the presence of the heptamer 5-ATGACGT-3. Transplacement of DNA fragments containing the ade6-M26 gene to other chromosomal loci has previously demonstrated that the heptamer functions in some, but not all, transplacements, suggesting that hot spot activity depends on chromosomal context. In this study, hot spot activity was tested in the absence of gross DNA changes by using site-directed mutagenesis to create the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…It is likely that both global and local controls are exerted by chromatin modifications, with the suppressing modifications being dominant. This type of model is consistent with the observation that hot spots moved to a novel chromosome context are often not hot spots (20).…”
Section: Vol 26 2006 Global Analysis Of Yeast Meiotic Recombinationsupporting
confidence: 75%
“…It is likely that both global and local controls are exerted by chromatin modifications, with the suppressing modifications being dominant. This type of model is consistent with the observation that hot spots moved to a novel chromosome context are often not hot spots (20).…”
Section: Vol 26 2006 Global Analysis Of Yeast Meiotic Recombinationsupporting
confidence: 75%
“…When no other mutations were present, we observed approximately 3,700 cds1 ϩ recombinants per million viable spores. This frequency of recombination is comparable to that observed for the ade6-M26 hot spot (12,17), which shows about the same frequency of meiotic DSBs (31). When M26 ES -I3 was also mutated in both parent strains by a single base pair change (cds1-2), the frequency of recombinants dropped 13-fold.…”
Section: Fig 2 Meiosis-inducedsupporting
confidence: 51%
“…This sequence is at least part of the binding site for a heterodimeric transcription factor, Atf1-Pcr1, which is also essential for M26 hot spot activity (22,36). When created by mutation of 1 to 4 bp, the M26 heptamer generates hot spots at multiple positions within the ade6 and ura4 genes (12), and all of those sites tested stimulate the formation of Rec12-dependent meiosis-specific DSBs near the site of the M26 heptamer (31). In addition to M26, Fox et al (13) showed that a closely related sequence, 5Ј-TGACGT C / A -3Ј, termed CRE (cyclic AMP response element), is also an Atf1-Pcr1-dependent hot spot at one site within the ade6 gene.…”
mentioning
confidence: 99%
“…As for transcriptional enhancers, the M26 site functions in a position-and orientation-independent fashion; each of eight M26 sites created by mutagenesis of one or a few base pairs has hot spot activity (11,14,31,41). Furthermore, while basal recombination does not require the Mts1-Mts2 heterodimer (Table 2) (20), hot spot activation does require components of the basal recombination machinery.…”
Section: Discussionmentioning
confidence: 99%